2019
DOI: 10.1002/adfm.201808979
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Fabrication of 3D Chiral Microwrinkles via Asymmetrical and Biaxial Bucklings

Abstract: Nano-and microsized chiral materials are receiving significant attention because of their unique characteristics, which include chiroptical activities and enantioselective interactions with living materials. However, the realization of chiral morphologies in such small-scale materials has been an issue because of the complicated fabrication methods and limited material selection. In this study, a facile and reproducible method is developed for fabricating 3D chiral microwrinkles with twisted shapes by asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 40 publications
(51 reference statements)
1
30
0
Order By: Relevance
“…8 It can indeed control the topology of the pattern accurately and is widely used in the nanofabrication of semiconductors. [9][10][11][12][13][14][15] Nonetheless, this approach is rather time-consuming and cost-ineffective, hampering its wide applications in different elds. 15,16 Therefore, the bottom-up synthesis is increasingly explored which promises to address the drawbacks of the top-down counterpart.…”
mentioning
confidence: 99%
“…8 It can indeed control the topology of the pattern accurately and is widely used in the nanofabrication of semiconductors. [9][10][11][12][13][14][15] Nonetheless, this approach is rather time-consuming and cost-ineffective, hampering its wide applications in different elds. 15,16 Therefore, the bottom-up synthesis is increasingly explored which promises to address the drawbacks of the top-down counterpart.…”
mentioning
confidence: 99%
“…In this respect, Hwang et al reported the formation of chiral wrinkles by a sequence of stretching-oxidation steps along two different axes. 78 However, such chiral structures are not appropriate as templates for plasmonic chirality in the visible-NIR range since their dimensions fall on the microscale. Considering that the mechanical properties of PDMS nanostructures may impose a limitation on the formation of stable patterns below 100 nm, further miniaturization of chiral wrinkles would lead to a gradual increase in both relevance and complexity.…”
Section: Templated Self-assembly Of Plasmonic Nps Into Chiral Morphol...mentioning
confidence: 99%
“…[1][2][3] Recently, an integration of nanoparticles with chirality (an asymmetric property by which an object is non-superposable on its mirror image) enables the formation of chiral nanoparticles (or CNPs) that have optical activity, denoting differential interactions with left-and right-handed (or LH and RH) circularly polarized light (CPL). [4] Producing CNPs unavoidably requires chiral stimulation from, e.g., chiral ligands, [5][6][7][8] chiral templates, [9][10][11] CPL, [12,13] helical magnetic fields, [14] orbital angular momentum, [15] macroscopic asymmetric gradients of biaxial strain fields, [16,17] and macroscopic shear forces. [18,19] An addition of chirality provides CNPs with various promising functions, such as ultrasensitive molecular detection and bioanalysis, [20][21][22] enhanced enantiodifferentiation, [23][24][25][26] active nanorheology, [27] polarization-dependent display, [14,28] enantioselective photocatalysis [29] and synthesis, [30][31][32] and enantiospecific bioapplications.…”
Section: Introductionmentioning
confidence: 99%